Global Mental Health and Neuroethics (Elsevier/Academic Press, 2020)
Global Mental Health and Neuroethics explores conceptual, ethical and clinical issues that have emerged with the expansion of clinical neuroscience into middle- and low-income countries. Conceptual issues covered include avoiding scientism and skepticism in global mental health, integrating evidence-based and value-based global medicine, and developing a welfarist approach to the practice of global psychiatry. Ethical issues addressed include those raised by developments in neurogenetics, cosmetic psychopharmacology and deep brain stimulation. Perspectives drawing on global mental health and neuroethics are used to explore a number of different clinical disorders and developmental stages, ranging from childhood through to old age.
English
Keywords: Neurosciences; mental health; neuroethics